Pengaruh Harga, Kualitas Pelayanan, dan Periklanan Terhadap Manfaat Koperasi Mahasiswa Universitas Negeri Padang (KOPMA UNP) Bagi Mahasiswa Universitas Negeri Padang (FE UNP) - Ervina Ervina; Bustari Muchtar; Rose Rahmidani (Jurnal Ecogen, 2018)
The purpose of this research was to find (1) The influece of Price, Quality Of Service and Advertising on the Benefits of KOPMA UNP For Students FE UNP (2) The Influence of Price on the Benefits of KOPMA UNP for Students FE UNP, (3) The Influence of Quality Of Service on the Benefits Of KOPMA UNP for Students FE UNP, (4) The Influence of Advertising On The Benefits of KOPMA UNP For Students FE UNP. This type of research was a descriptive associative. The populations of this research were student of FE UNP who has transacted at KOPMA UNP. The Sampling was determined by Wibisono formula with a total sample of 100 people and using accidental sampling technique. The type of data in this research was primary data. The data has been collected and then analyzed statistically with multiple linear regression analysis using SPSS version 16.0. Hypothesis test in this research have done by using F test and t test. The result of research shows that (1) The influence of Price, Quality Of Service and Advertising Simultaneosly has positive and significant effect to KOPMA UNP On The Benefits for Student of FE UNP with significance value 0.000 <0.05, (2) The Price has positive and significant Effect On The Benefits Of KOPMA UNP for Student FE UNP with significance value of 0.009 <0.05, (3) The Quality of Service has not significant effect On The Benefits Of KOPMA UNP for Student FE UNP with significance value 0.078> 0.05, (4) The Advertising has not effect On Benefits Of KOPMA UNP For Students FE UNP with significance value 0.864 > 0.05. Keywords              : Price, Quantity Of Service, Advertising and Benefits